Method and theory in the study of religion : working papers from Hannover - Führding, Steffen, 1981- (Supplements to Method & Theory in the Study of Religion, 2017)
Since the downfall of the phenomenology of religion as the leading paradigm in the study of religion in the 1960s, theoretical and methodological discussions surrounding the nature and identity of the study of religion as an academic discipline have proliferated. The essays included in this volume approach these debates from a variety of angles. Based on a series of talks held at the University of Hannover over the last few years, the essays are intended to be understood as diagnostic works in progress and thus as working papers, all of which strive to point out important problems and perspectives in the field of theories and methodology and to draw attention to the future of the discipline. Using developments in Hanover as a launch pad, the volume forms the basis for further insights into the direction of the study of religion as a discipline at large.